Profit as a means or an end? A conceptual framework for an ecological economics approach to sustainable business - Jennifer B. Hinton; Sarah E. Cornell (Post-growth Economics Network (PEN), 2022)
This paper examines the implications of the argument that sustainable businesses should see profit as a means, not an end. It develops a heuristic conceptual framework that identifies two main ways in which a business can treat profit as an end: first, through voluntary objectives; and secondly, through private financial rights. To illustrate the usefulness of this framework, these indicators are applied to examine a range of theoretical approaches, incorporation structures, and third-party certifications that have been developed with the aim of making business sustainable. The application of the framework reveals inconsistencies, ambiguities, and shortfalls of these approaches in their treatment of profit, and outlines ways to advance the theory and practice of sustainable business.
Keywords: 330; Sustainable business; Social enterprise; Sustainable economy; Ecological economics; Degrowth